2017
DOI: 10.1016/j.jpainsymman.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Complicated Grief and Depression in Bereaved Caregivers: A Nationwide Prospective Cohort Study

Abstract: Severe preloss grief and depressive symptoms were key predictors of postloss complicated grief and depressive symptoms. Systematic assessment may identify caregivers with a high risk profile who need targeted support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
172
3
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(197 citation statements)
references
References 47 publications
15
172
3
7
Order By: Relevance
“…Gilbar and Ben‐Zur, Kim et al, and Song et al sampled cancer patients identified by state registries; Nielsen et al sampled patients registered with drug reimbursement. Two studies achieved a representative sample. All other studies used convenience samples from one or more treatment or care institutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gilbar and Ben‐Zur, Kim et al, and Song et al sampled cancer patients identified by state registries; Nielsen et al sampled patients registered with drug reimbursement. Two studies achieved a representative sample. All other studies used convenience samples from one or more treatment or care institutions.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies exclusively addressed caregivers whose relatives died of cancer, with the exception of 3 studies by Kapari et al, Nielsen et al, and Brazil et al, where cancer patients accounted for 96%, 90%, and 82% of the samples, respectively. Two of those studies controlled for diagnosis and found no significant association with the respective outcome measures …”
Section: Resultsmentioning
confidence: 99%
“…Severe pre‐loss grief and depressive symptoms may be predictors of post‐loss complicated grief and depressive symptoms. Systematic assessment may identify caregivers at risk (Nielsen et al, ).…”
Section: The Studymentioning
confidence: 99%
“…There is variation in the frequency, duration and intensity with which individuals experience grief reactions. Approximately 7–10% of individuals will experience an extreme and prolonged reaction, termed Prolonged Grief (PG; or complicated grief or Persistent Complex Bereavement Disorder; American Psychiatric Association, 2013; Maciejewski, Maercker, Boelen, & Prigerson, 2016; Nielsen et al, 2016; Prigerson et al, 2009; Shear et al, 2011). PG has received increased attention in recent years as it is linked with a range of negative health outcomes independent of bereavement-related depression or anxiety (Bonanno et al, 2007; Maciejewski et al, 2016; Prigerson et al, 2009; Shear et al, 2011) and shows better outcomes in response to grief-targeted treatments (Bryant et al, 2014; Shear, Frank, Houck, & Reynolds, 2005; Shear et al, 2016).…”
mentioning
confidence: 99%